Friendly hospital services from the adolescents point of view - Migdalia Fernández Villalón; Reinaldo Reyes Mediaceja; Emma Bastart Ortiz (Centro Provincial de Información de Ciencias Médicas, 2017)
A descriptive and cross-sectional investigation of 1 630 adolescents admitted to "Dr. Antonio María Béguez César" Southern Teaching Children Hospital was carried out in Santiago de Cuba, from January to December, 2015, aimed at identifying their expectations regarding a friendly care in hospital services, determining the preparation of doctors and nurses and describing the structure and organizational conditions of hospitalization wards.  To such an effect surveys to adolescents and a questionnaire to doctors were applied to check their knowledge; the performance of doctors and nurses staff was also evaluated by means of an observation guide.  Among the analyzed aspects of the series, the sanitary staff kindness (83.5%) and wards privacy (60.8%) were very important for adolescents.  Likewise, it was observed that most of the doctors possessed appropriate knowledge (86.6%) to care these patients and that all of them had an acceptable performance; however, some difficulties in the structure and  organizational conditions of the wards were detected, so it was concluded that the hospital institution didn't fulfill  the necessary conditions to be qualified as friendly.